A song and dance: branded entertainment and mobile promotion - Grainge, Paul (Sage, 2012)
This article considers the rise of branded entertainment within the contemporary marketing and media environment. Specifically, it examines how mobile phone marketing in the UK has sought to engage consumers and perform the social use of mobile technology through multimedia ad campaigns with an inscribed entertainment value. Focusing on brand campaigns for 3G mobile services that borrow explicitly from reality television (T-Mobile) and Hollywood film (Orange), the article explores the concept of branded entertainment in relation to the ‘popular imagination’ of mobile communication in the late 2000s. In doing so, it examines the particular relation of flash mobs to the production of brand community.